Design and evaluation of network mobility protocol to achieve seamless handoff - Hassan Abdalla Hashim, Aisha (s.n, 2012)
Network Mobility Basic Support Protocol(NEMO BSP) is an extension of Mobile IPv6(MIPv6)taht inherits all the drawbacks of Mobile IPv6, such as inefficient routing path, single point of failure, high handoff latency, packet loss, and high packet overhead. Therefore, route optimization, delay during handoff as well as multihoming technique in NEMO is becoming most important area for current researcher. The objective of this project is to achieve the Seamless Handoff by proposing a Macro Mobility Scheme in NEMO network (MM-NEMO) in order to reduce packet loss and delay during handoff from one domain to another.